d-chiro-Inositol Ribophostin: A Highly Potent Agonist of d-myo-Inositol 1,4,5-Trisphosphate Receptors: Synthesis and Biological Activities - Mills, Stephen J. (J Med Chem, 2020)
[Image: see text] Analogues of the Ca(2+)-releasing intracellular messenger d-myo-inositol 1,4,5-trisphosphate [1, Ins(1,4,5)P(3)] are important synthetic targets. Replacement of the α-glucopyranosyl motif in the natural product mimic adenophostin 2 by d-chiro-inositol in d-chiro-inositol adenophostin 4 increased the potency. Similar modification of the non-nucleotide Ins(1,4,5)P(3) mimic ribophostin 6 may increase the activity. d-chiro-Inositol ribophostin 10 was synthesized by coupling as building blocks suitably protected ribose 12 with l-(+)-3-O-trifluoromethylsulfonyl-6-O-p-methoxybenzyl-1,2:4,5-di-O-isopropylidene-myo-inositol 11. Separable diastereoisomeric 3-O-camphanate esters of (±)-6-O-p-methoxy-benzyl-1,2:4,5-di-O-isopropylidene-myo-inositol allowed the preparation of 11. Selective trans-isopropylidene deprotection in coupled 13, then monobenzylation gave separable regioisomers 15 and 16. p-Methoxybenzyl group deprotection of 16, phosphitylation/oxidation, then deprotection afforded 10, which was a full agonist in Ca(2+)-release assays; its potency and binding affinity for Ins(1,4,5)P(3)R were similar to those of adenophostin. Both 4 and 10 elicited a store-operated Ca(2+) current I(CRAC) in patch-clamped cells, unlike Ins(1,4,5)P(3) consistent with resistance to metabolism. d-chiro-Inositol ribophostin is the most potent small-molecule Ins(1,4,5)P(3) receptor agonist without a nucleobase yet synthesized.